2019
DOI: 10.1039/c9sc03172c
|View full text |Cite
|
Sign up to set email alerts
|

A Cu–Pd single-atom alloy catalyst for highly efficient NO reduction

Abstract: Highly active and selective NO reduction was achieved at low temperatures using a minimum amount of noble metal Pd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 55 publications
3
89
0
Order By: Relevance
“…The high activity of Cu-based SAAs toward numerous chemical reactions has been experimentally confirmed. 4,11,14 We determine that, among the Cu-based SAAs, Ni/Cu and Rh/Cu bimetallic alloys exhibit the lowest dissociation barriers. The most facile bond cleavage reactions are predicted to occur on Ni/Cu surfaces (Fig.…”
Section: Highly Reactive Ni and Rh Ensembles On Cu-based Alloysmentioning
confidence: 96%
See 2 more Smart Citations
“…The high activity of Cu-based SAAs toward numerous chemical reactions has been experimentally confirmed. 4,11,14 We determine that, among the Cu-based SAAs, Ni/Cu and Rh/Cu bimetallic alloys exhibit the lowest dissociation barriers. The most facile bond cleavage reactions are predicted to occur on Ni/Cu surfaces (Fig.…”
Section: Highly Reactive Ni and Rh Ensembles On Cu-based Alloysmentioning
confidence: 96%
“…12 Accordingly, the work of Zhang et al 11 is a testament to the unique catalytic properties offered by isolated reactive atoms doped on less reactive host materials. 13 In addition, very recent studies by Furukawa and co-workers highlight that Pd/Cu SAA nanoparticles supported on Al 2 O 3 are exceptional catalysts for the catalytic NO reduction by CO. 14 The latter reaction is crucial for stripping out harmful gases from catalytic converters. 15 In particular, the authors demonstrated that on a Pd/Cu SAA catalyst, NO was fully converted to N 2 at low temperatures (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGMs have been proven efficient catalysts for SCR of NO in the presence of reducing agents, such as CO, H2, NH3, and HC. However, proper SCR is still challenging as it requires the development of catalysts characterized by: (i) good low-temperature catalytic activity, (ii) minimum use of PGMs, and (iii) elevated N2 selectivity and low N2O production [118,119]. Nevertheless, the simultaneous resolution of these issues remains very difficult.…”
Section: Nox Reduction Reactionmentioning
confidence: 99%
“…It is well known that the group IB metals (Au, Ag, and Cu) are very capable for reduction of NO, such as Cu-exchanged sieve. Thus, some studies have used Cu as an inert element to modify the electronic factors of Pd and yield Cu5Pd/Al2O3 SAA catalyst with a much higher NO conversion and N2 selectivity than Cu/Al2O3 and Pd/Al2O3 catalysts in the presence of O2 and O2 + C3H6 [119]. However, NO conversion declined with time since some active sites became occupied by CO and C3H6 oxidation.…”
Section: Nox Reduction Reactionmentioning
confidence: 99%